Tannic acid-Fe3+ activated rapid polymerization of ionic conductive hydrogels with high mechanical properties, self-healing, and self-adhesion for flexible wearable sensors. (12th April 2022) - Wang, Jing; Dai, Tianyi; Wu, Hao; Ye, MingYu; Yuan, Guoliang; Jia, Hongbing
Abstract: Wearable sensors based on hydrogels have been rapidly developed in many fields such as electronic skin, health detection, and human-machine interface. Wearable sensors for real-time monitoring of human activities require hydrogels with desirable mechanical strength, self-healing ability, sensing stability, and self-adhesion. However, to meet all these mentioned requirements, the preparation process of hydrogels is always complicated and time-consuming. Herein, rapid polymerization hydrogels (PATG-B-Fe) for wearable sensors were designed from bacterial cellulose nanowhisker (BCW), tannic acid (TA), polyacrylic acid (PAA), Fe 3+ and glycerol/water (Gly/H2 O). The dual catalysis system of TA-Fe 3+ and Gly remarkably shortened the reaction time to 4 s at ambient temperature. With multiple hydrogen bonds and coordination among BCW-TA, PAA, and Fe 3+, hydrogels exhibited an excellent trade-off between mechanical (stress of 203 kPa, elongation at break of 1950%) and self-healing property (91% of efficiency). Strain sensors based on PATG-B-Fe hydrogels had good sensitivity (Gauge factor, maximum GF = 5.2 in 1200–1900% strain) and stable sensing properties at a wide temperature range (−20–60 °C). Furthermore, strain sensors were adhered directly to skin to monitor large and subtle human movements. We believe PATG-B-Fe sensors may be a new horizon for the development of wearable and flexible electronic devices in the future. Graphical abstract: Image 1 Highlights: Dual catalysis system makes gel reaction finish in 4 s with no extra energy. Hydrogel has high mechanical strength and excellent self-healing property. Hydrogel has good self-adhesive and sticks firmly to various material surface. Sensor has stable sensing properties at a wide temperature range (−20 to 60 °C). Sensor has good sensitivity and can monitor large and subtle human movements.